Approaching the matched filter bound with block transmission techniques - Silva, Fábio (2018)
Block transmission techniques, with appropriate cyclic prefixes and employing frequency-domain equalisation techniques, have been shown to be suitable for high data rate transmission over severely time-dispersive channels. The most popular techniques based on this concept are orthogonal frequency division multiplexing (OFDM) and single-carrier with frequency-domain equalisation (SC-FDE). In this paper, we consider OFDM and SC-FDE transmission schemes and study the impact of the number of multipath components and the diversity order on their performance. It is shown that when we have a high number of separable multipath components, the asymptotic performance of both schemes approaches the matched filter bound, even without diversity. When we have diversity, the performance approaches the matched filter bound faster, with a small number of separable multipath components. It was also observed that the SC-FDE has an overall performance advantage over the OFDM option, especially when employing the iterative block decision feedback equaliser with turbo equalisation and for high code rates.